Modulation of virulence and metabolic profiles in Klebsiella pneumoniae under indole-mediated stress response - Fang, Xueyao; Chen, Yanhui; Hu, Longhua; Gu, Shumin; Zhu, Junqi; Hang, Yaping; Cao, Xingwei; Xiao, Yanping; Luo, Hong; Zhao, Chuwen; Xiao, Lianhua; Zhong, Qiaoshi (Frontiers in Cellular and Infection Microbiology, 2025)
Indole, a crucial bacterial signaling molecule, plays a fundamental role in regulating various physiological processes within bacteria, including growth, acid tolerance, biofilm development, motility, and other cellular functions. Its regulatory influence extends beyond indole-producing bacteria, significantly impacting the physiological activities in non-indole-producing species. In this study, we demonstrate that indole enhances the pathogenicity and viability of Klebsiella pneumoniae using the Galleria mellonella infection model and serum killing assay. Concurrently, indole has varying effects on biofilm formation in K. pneumoniae, with some strains showing enhanced biofilm formation ability. To elucidate the underlying molecular mechanisms, transcriptome analysis revealed that indole exposure in K. pneumoniae led to the upregulation of genes associated with pili formation and iron acquisition systems, while simultaneously inducing oxidative stress responses. Additionally, our analysis uncovered extensive metabolic remodeling. Specifically, we observed significant upregulation of genes involved in simple carbohydrate utilization pathways, including those responsible for galactose, mannose, and maltose metabolism, as well as enhanced expression of genes associated with pyrimidine biosynthesis. These findings collectively indicate that indole enhances the intestinal colonization and pathogenicity of K. pneumoniae primarily by modulation of fimbriae expression and metabolic pathway regulation.